Safe Micromobility. - (:unkn) unknown (My University, 2020)
This report examines the traffic safety of pedal cycles, electrically assisted cycles and electrically powered personal mobility devices such as e-scooters, whether owned or shared, in an urban context. In a fastevolving urban transport environment, micromobility is changing how people move on a daily basis. The report proposes a framework to define micromobility which includes all the above vehicles and suggests certain limits on mass and speed to classify them. It also compares the safety of powered standing scooters (e-scooters) to that of bicycles, mopeds and motorcycles. The report defines micromobility as the use of vehicles with a mass of less than 350 kg and a design speed of 45 km/h orless. This definition limits the kinetic energy of such micro-vehicles to 27 kJ, one hundred times less than the kinetic energy reached by a compact car at top speed. The report classifies micro-vehicles into four types based on their speed and mass: Type A micro-vehicles have a mass of up to 35 kg and their power supply (if any) is electronically limited so the vehicle speed does not exceed 25 km/h (15.5 mph). Many bicycles, e-bikes, e-scooters and self-balancing vehicles fall into this category.The report proposes a range of safety improvements for micromobility. These relate to vehicle design, fleet operation, infrastructure, regulatory enforcement and training. It proposes future-proof, balanced safety regulations proportional to the risks imposed. The analysis draws on the results of a workshop attended by 40 participants from 15 countries in October 2019.
Keywords: Verkehrssicherheit; Fahrradverkehr; Elektromobilität; Klassifizierung; Gefahrenanalyse; Autoverkehr; Risikovorsorge; Mikromobilität